The Lintner-Butters Analysis of the Effect of Mergers on Industrial Concentration, 1940-1947: Rejoinder to Dr. Weston - Lintner, John; Butters, J. Keith (The Review of Economics and Statistics, 1951)
John Lintner, J. Keith Butters, The Lintner-Butters Analysis of the Effect of Mergers on Industrial Concentration, 1940-1947: Rejoinder to Dr. Weston, The Review of Economics and Statistics, Vol. 33, No. 1 (Feb., 1951), pp. 73-75